CONSTRUCTING ONLINE BASED HISTORY LEARNING: COMPARISON OF LEARNING CONTENT MANAGEMENT SYSTEM (LCMS) TO LEARNING MANAGEMENT SYSTEM (LMS) - Kamarga, Hansiswany (Historia: Jurnal Pendidik dan Peneliti Sejarah, 2011)
The purpose of this paper is to find a comparison between the use of QuestGarden learning content management system and Edmodo learning management system in learning particularly for the teaching of history. Characteristics of history filled with facts mastery often make teacher forget the real purpose of history learning. The abundance of facts characteristics brought up in history teaching, so it often put history learning as facts mastery learning through rote learning activity. This writing attempt to lift other approach in history learning namely online based learning that was identified can improve the ability to think. The results show QuestGarden (LCMS) or Edmodo (LMS) can be implemented in the history teaching learning, though both have different characters and use. Teachers need to understand them so that they can implement it in a synergic position.